Social reincorporation of FARC-EP's former combatants: The case of the Colombian Peace Agreement 2016 - Cruz, Ana Rita Rosário da Silva (2021)
Four years after the implementation of the 2016 Peace Agreement in Colombia, this dissertation evaluates the development of the measures related to the social reincorporation of the FARC-EP into the community. The social reincorporation of former combatants was considered, since the beginning of the debates on the Agreement, as one of the key factors for the success and consolidation of the peace process. The study uses a triangulation method that includes document analysis and interviews, stemming from fieldwork in Colombia, supported by scientific articles and meetings, as well as nonparticipant observation in conferences. This work analyses the perceptions of the actors involved and the guerrilla who seeks to reincorporate into a social life within a legal framework. Although the existing literature is critical about the degree of success, this work shows that social reincorporation, in general, is being achieved, with some exceptions in which the Agreement likely will have to be adapted to the current needs and urgencies.